Thermodynamic modeling of hydrogen–water systems with gas impurity at various conditions using cubic and PC-SAFT equations of state - Amer Alanazi; Saleh Bawazeer; Muhammad Ali; Alireza Keshavarz; Hussein Hoteit (Energy Conversion and Management: X, 2022)
Hydrogen (H2) has emerged as a viable solution for energy storage of renewable sources, supplying off-seasonal demand. Hydrogen contamination due to undesired mixing with other fluids during operations is a significant problem. Water contamination is a regular occurrence; therefore, an accurate prediction of H2-water thermodynamics is crucial for the design of efficient storage and water removal processes. In thermodynamic modeling, the Peng–Robinson (PR) and Soave Redlich–Kwong (SRK) equations of state (EoSs) are widely applied. However, both EoSs fail to predict the vapor-liquid equilibrium (VLE) accurately for H2-blend mixtures with or without fine-tuning binary interaction parameters due to the polarity of the components. This work investigates the accuracy of two advanced EoSs: the Schwartzentruber and Renon modified Redlich–Kwong cubic EoS (SR-RK) and perturbed-chain statistical associating fluid theory (SAFT) in predicting VLE and solubility properties of H2 and water. The SR-RK involves the introduction of polar parameters and a volume translation term. The proposed workflow is based on optimizing the binary interaction coefficients using regression against experimental data that cover a wide range of pressure (0.34 to 101.23 MPa), temperature (273.2 to 588.7 K), and H2 mole fraction (0.0004 to 0.9670) values. A flash liberation model is developed to calculate the H2 solubility and water vaporization at different temperature and pressure conditions. The model captures the influence of H2-gas (CO2) impurity on VLE. The results agreed well with the experimental data, demonstrating the model’s capability of predicting the VLE of hydrogen-water mixtures for a broad range of pressures and temperatures. Optimized coefficients of binary interaction parameters for both EoSs are provided. The sensitivity analysis indicates an increase in H2 solubility with temperature and pressure and a decrease in water vaporization. Moreover, the work demonstrates the capability of SR-RK in modeling the influence of gas impurity (i.e., H2–CO2 mixture) on the H2 solubility and water vaporization, indicating a significant influence over a wide range of H2–CO2 mixtures. Increasing the CO2 ratio from 20% to 80% exhibited almost the opposite behavior of H2 solubility compared to the pure hydrogen feed solubility. Finally, the work emphasizes the critical selection of proper EoSs for calculating thermodynamic properties and the solubility of gaseous H2 and water vaporization for the efficient design of H2 storage and fuel cells.